The Oxford handbook of the archaeology of the Levant : c. 8000-332 BCE (Oxford handbooks., 2014)
"This Handbook aims to serve as a research guide to the archaeology of the Levant, an area situated at the crossroads of the ancient world that linked the eastern Mediterranean, Anatolia, Mesopotamia, and Egypt. The Levant as used here is a historical geographical term referring to a large area which today comprises the modern states of Israel, Jordan, Lebanon, western Syria, and Cyprus, as well as the West Bank, Gaza, and the Sinai Peninsula. Unique in its treatment of the entire region, it offers a comprehensive overview and analysis of the current state of the archaeology of the Levant within its larger cultural, historical, and socio-economic contexts. The Handbook also attempts to bridge the modern scholarly and political divide between archaeologists working in this highly contested region" -- Jacket.